2005
DOI: 10.1016/j.pnpbp.2004.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Platelet serotonin uptake and paroxetine binding among allelic genotypes of the serotonin transporter in alcoholics

Abstract: Expression rates of long (L) and short (S) alleles of the serotonin (5-HT) transporter (5-HTT) gene have been shown to differ under various circumstances. We compared 5-HTT uptake (function) level and paroxetine binding (density) in platelets of alcoholics as indices of 5-HTT expression rate among LL, LS, and SS genotypes. Concentration curves of [ 3 H]5-HT and [ 3 H]paroxetine were used to quantify the equilibrium constant (Km) and maximum 5-HT uptake rate (Vmax) for 5-HTT uptake into intact platelets and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
4
10
1
Order By: Relevance
“…Before BLT, 5-HTT turnover numbers and E TYR correlated significantly in patients achieving full remission (r ¼ 0.624, p ¼ 0.002), at a trend level in partial responders (r ¼ 0.482, p ¼ 0.069), while there was no correlation in nonresponders (r ¼ 0.083, p ¼ 0.729). The 5-HTTLPR polymorphism was not associated with any of the functional 5-HTT parameters, and in contrast to some (Greenberg et al, 1999;Patkar et al, 2003), but not other findings (Javors et al, 2005), our data failed to show an influence of 5-HTTLPR on seasonal variations in V max or other 5-HTT parameters.…”
Section: Discussioncontrasting
confidence: 99%
“…Before BLT, 5-HTT turnover numbers and E TYR correlated significantly in patients achieving full remission (r ¼ 0.624, p ¼ 0.002), at a trend level in partial responders (r ¼ 0.482, p ¼ 0.069), while there was no correlation in nonresponders (r ¼ 0.083, p ¼ 0.729). The 5-HTTLPR polymorphism was not associated with any of the functional 5-HTT parameters, and in contrast to some (Greenberg et al, 1999;Patkar et al, 2003), but not other findings (Javors et al, 2005), our data failed to show an influence of 5-HTTLPR on seasonal variations in V max or other 5-HTT parameters.…”
Section: Discussioncontrasting
confidence: 99%
“…The current study is the first to show that the reduced activity of the 5-HTT in human alcoholics is related to drinking patterns and that this can be demonstrated in platelet preparations. We previously reported reduced 5-HT uptake in the platelets of a smaller sample of LL alcoholics (Javors et al, 2005). The current study substantially expands those findings, clearly showing reduced functional 5-HTT uptake in L-carriers, and adds the findings of reduced paroxetine binding as well.…”
Section: Discussionsupporting
confidence: 82%
“…The observed lack of correlation between V max and B max in our study probably is due in part to this lack of specificity of paroxetine binding. However, our unpublished results have indicated that only about 20% of the 5-HTTs are located at the surface of platelets, which may further account for the observed lack of correlation between V max and B max (Javors et al, 2005). Although the density of paroxetine binding (B max ) is certainly an indicator of the expression rate of the 5-HTT, the mechanism by which the majority of transporters are internalized is unknown, but it is likely to include phosphorylation, glycosylation, and other cellular signaling mechanisms involved with 5-HTT uptake and turnover.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…has not been addressed unequivocally, even though a dominant s allele effect has been repeatedly reported [34][35][36] other studies did not confirm this model 37 and SNPs are usually supposed to have a codominant effect. 38 Our results favour the view of a dominant s effect, as indicated on response and early response.…”
Section: -Httlpr and Ssri Meta-analysismentioning
confidence: 94%